A Prussian blue analogue and its preparation method and application

By employing an anhydrous eutectic solvent to control crystallization and particle size, the synthesis of Prussian blue analogues achieves reduced defects and improved electrochemical performance.

CN116253334BActive Publication Date: 2024-12-31CAMEL GRP WUHAN OPTICS VALLEY R&D CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211439935.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2024-12-31
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

Existing synthesis methods for Prussian blue analogues struggle to balance anhydrous synthesis, nanosizing, and low defect formation, leading to reduced capacity and poor conductivity due to high crystal water content and defects.

Method used

A method involving the use of an anhydrous eutectic solvent to synthesize Prussian blue analogues, leveraging high viscosity to control crystallization rate and particle size, resulting in low-defect, nano-sized particles.

Benefits of technology

The method effectively reduces crystal water content and defects, enhancing sodium storage kinetics and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253334B_ABST
    Figure CN116253334B_ABST
Patent Text Reader

Abstract

The invention discloses a Prussian blue analogue and a preparation method and application thereof. The preparation method of the Prussian blue analogue comprises the following steps: mixing raw materials for forming a low eutectic solvent, heating to a target temperature, and obtaining a high-viscosity liquid low eutectic solvent; mixing the high-viscosity liquid low eutectic solvent with sodium ferrocyanide and an optional metal salt at the target temperature, and obtaining high-quality Na x M[Fe(CN)6] y □ 1‑y ·zH2O. The present invention utilizes an anhydrous low eutectic solvent to synthesize a Prussian blue analogue, which reduces the crystal water content in the product on the one hand, and utilizes the high viscosity of the low eutectic solvent to reduce the nucleation rate of the product on the other hand, thereby synthesizing low-defect and nano-sized particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of the preparation of Prussian blue analogues, and in particular to a Prussian blue analogue, a preparation method thereof, and an application thereof. Background Art

[0002] Prussian blue and its analogues (PBAs) are important cathode materials for sodium-ion batteries, and their general structural formula is Na x M[Fe(CN)6] y □ 1-y ·zH2O (0 < x < 2, 0 < y < 1), where M represents a transition metal, □ represents a vacancy defect, and z represents crystal water. Its structural characteristics are that metal ions M and Fe are alternately arranged and connected with C≡N to form a rigid open framework structure –Fe–C≡N–M–. The interstitial positions in this open structure can accommodate a certain amount of Na + and water molecules, and form large three-dimensional ion channels in the

[100] direction, facilitating the rapid insertion and extraction of sodium ions.

[0003] The synthesis of PBAs usually adopts the aqueous phase co-precipitation method and the hydrothermal method. Patent document CN103474659B discloses a preparation method and an application of a cathode material for a sodium-ion battery, and specifically discloses that the preparation method of the Prussian blue complex composite material provided by it at least includes: uniformly dispersing a transition metal salt, an acid and a reducing agent in water to obtain a reaction solution, and heating the solution in a protective atmosphere for a period of time to obtain the Prussian blue complex material. However, in an aqueous solution, soluble metal salts react with Na4Fe(CN)6 rapidly to nucleate and grow, resulting in more defects and more crystal water (z > 2) in the synthesized Prussian blue structure. Among them, the defects reduce the capacity of Prussian blue, and the crystal water is prone to side reactions during the electrochemical cycling process. In addition, the conductivity of PBAs is very poor. In order to improve their electrochemical kinetic performance, reducing their particle size is also an effective method. For this reason, a large amount of additives (such as sodium citrate, sodium chloride, etc.) are usually added during the synthesis of PBAs to inhibit the growth rate of PBAs, so as to synthesize nano-PBAs with low defects and low crystal water content, but the existing means will greatly increase the preparation cost of PBAs. The literature synthesizes Prussian blue in an ionic liquid (Dalton Trans., 2015, 44, 12878). Although it avoids the influence of crystal water, its crystallization rate is not effectively inhibited, resulting in more defects in the product.

[0004] It can be seen that in the current synthesis methods of Prussian blue, how to balance anhydrous synthesis, nanosizing and low defect formation is still a difficult problem. Summary of the Invention

[0005] The object of the present invention is to overcome the above technical deficiencies, and to provide a Prussian blue analogue, a preparation method and an application thereof, so as to solve the technical problem that the anhydrous synthesis, nanosizing and low defect formation cannot be兼顾 in the synthesis method of Prussian blue in the prior art.

[0006] The first aspect of the present invention provides a preparation method of a Prussian blue analogue, comprising the following steps:

[0007] Mix the raw materials for forming the eutectic solvent, and heat to the target temperature to obtain a high-viscosity liquid eutectic solvent;

[0008] Mix the above high-viscosity liquid eutectic solvent with sodium ferrocyanide (Na4Fe(CN)6) and an optional metal salt at the target temperature, and after washing and drying, obtain high-quality Na x M[Fe(CN)6] y □ 1-y ·zH2O;

[0009] wherein, M is at least one of transition metals Fe, Cu, Ni, Mn and Co, □ is a low-spin vacancy defect, 0 < x < 2, 0 < y < 1, 0 < z < 2; the target temperature is 5 to 35 °C above the melting point of the eutectic solvent.

[0010] The second aspect of the present invention provides a Prussian blue analogue, which is obtained by the preparation method of the Prussian blue analogue provided in the first aspect of the present invention.

[0011] The third aspect of the present invention provides an application of a Prussian blue analogue, and the Prussian blue analogue is applied as a positive electrode material of a sodium ion battery.

[0012] Compared with the prior art, the beneficial effects of the present invention include:

[0013] The present invention uses an anhydrous eutectic solvent to synthesize a Prussian blue analogue. On the one hand, the content of crystal water in the product is reduced. On the other hand, the high viscosity of the eutectic solvent is used to reduce the nucleation rate of the product, and low-defect and nano-sized particles can be synthesized. Description of the Drawings

[0014] Figure 1 XRD pattern of Fe-PBAs synthesized in Example 1 of the present invention;

[0015] Figure 2 SEM photograph of Fe-PBAs synthesized in Example 1 of the present invention;

[0016] Figure 3 SEM photograph of Fe-PBAs synthesized in Comparative Example 1 of the present invention;

[0017] Figure 4 The charge and discharge curve of the Fe-PBAs synthesized in Example 1 of the present invention at a rate of 0.2C (1C = 170 mA / g);

[0018] Figure 5 The charge and discharge curve of the Fe-PBAs synthesized in Example 1 of the present invention at a rate of 5C (1C = 170 mA / g);

[0019] Figure 6 The charge-discharge curve of Fe-PBAs synthesized in Comparative Example 1 of the present invention at a rate of 0.2C (1C = 170 mA / g);

[0020] Figure 7 This is the charge and discharge curve of the Fe-PBAs synthesized in Comparative Example 1 of the present invention at a rate of 5C (1C=170mA / g). DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0022] The first aspect of the present invention provides a method for preparing a Prussian blue analogue, comprising the following steps:

[0023] S1: mixing raw materials for forming a low eutectic solvent, heating to a target temperature, and obtaining a high-viscosity liquid low eutectic solvent;

[0024] S2: The high viscosity liquid eutectic solvent is mixed with sodium ferrocyanide (Na4Fe(CN)6) and an optional metal salt at a target temperature to obtain high quality Na x M[Fe(CN)6] y □ 1-y · zH2O;

[0025] Wherein, M is at least one of transition metals Fe, Cu, Ni, Mn and Co, □ is a low-spin vacancy defect, 0 <x<2,0<y<1,0<z<2。

[0026] The inventors found that when synthesizing Prussian blue analogs, the prior art only considers anhydrous synthesis, but fails to regulate the crystallization rate. The present invention uses an anhydrous deep eutectic solvent as a medium to achieve the synthesis of PBAs, making full use of the characteristic that the viscosity of the deep eutectic solvent increases with decreasing temperature. When the viscosity is high, the crystallization rate can be effectively reduced, thereby controlling the number of defects and particle size. Not only can highly crystalline nano PBAs materials be synthesized, but the content of crystal water in the material can also be effectively reduced, thereby enhancing its sodium storage kinetics.

[0027] In the present invention, the melting point of the low eutectic solvent is 60 to 85° C., preferably 65 to 80° C. Low eutectic agents with too low or too high melting points are difficult to obtain or prepare, have high costs, and are not suitable for synthesizing Prussian blue.

[0028] In some preferred embodiments of the present invention, the deep eutectic solvent is a deep eutectic solvent containing an organic acid or an alcohol. The present invention is more conducive to enhancing the solubility of the metal salt by selecting the above-mentioned deep eutectic solvent.

[0029] In some specific embodiments of the present invention, the organic acid is citric acid and the alcohol is ethylene glycol.

[0030] In some more specific embodiments of the present invention, the deep eutectic solvent is a citric acid + 1,3-bis(hydroxymethyl)urea deep eutectic solvent or an ethylene glycol + choline chloride deep eutectic solvent.

[0031] In some more specific embodiments of the present invention, the deep eutectic solvent is a deep eutectic solvent formed by 40 wt % of citric acid and 60 wt % of 1,3-bis(hydroxymethyl)urea (melting point is 65° C.), or a deep eutectic solvent formed by 50 wt % of ethylene glycol and 50 wt % of choline chloride (melting point is 80° C.).

[0032] In the present invention, the mass ratio of sodium ferrocyanide, metal salt and deep eutectic solvent is (20-100):(0-100):100.

[0033] In the present invention, the metal salt includes metal chloride or metal sulfate. Further, the metal chloride includes at least one of FeCl2, CuCl2, CoCl2, MnCl2, and NiCl2, and the metal sulfate includes at least one of FeSO4, CuSO4, CoSO4, MnSO4, and NiSO4.

[0034] In the present invention, the target temperature is 5 to 35° C. above the melting point of the low eutectic solvent, preferably 5 to 20° C. If the target temperature is too high, the synthesized Prussian blue analogue has a large particle size and may even be at risk of decomposition due to the high temperature; if the target temperature is too low, the solution viscosity is too high, resulting in difficulty in stirring.

[0035] In the present invention, the high viscosity liquid eutectic solvent is mixed with sodium ferrocyanide (Na4Fe(CN)6) and an optional metal salt at a target temperature to react, comprising:

[0036] A high viscosity liquid eutectic solvent is stirred and reacted with sodium ferrocyanide (Na4Fe(CN)6) and an optional metal salt at a target temperature for 8 to 24 hours, and then allowed to stand and age for 8 to 24 hours at the target temperature. The present invention allows the sodium ferrocyanide and the optional metal salt to be fully mixed by stirring to form nuclei; and allows the product nuclei to grow and further react by standing and aging.

[0037] In some preferred embodiments of the present invention, the above-mentioned Na x M[Fe(CN)6] y □ 1-y · In zH2O, 1 <x<2,0.9<y<1,0<z<1。

[0038] In some preferred embodiments of the present invention, the size of the Prussian blue analogue is 10 to 100 nm, preferably 30 to 50 nm.

[0039] The second aspect of the present invention provides a Prussian blue analogue, which is obtained by the preparation method of the Prussian blue analogue provided by the first aspect of the present invention.

[0040] A third aspect of the present invention provides an application of a Prussian blue analogue, wherein the Prussian blue analogue is applied as a positive electrode material for a sodium ion battery.

[0041] To avoid redundancy, in the following embodiments and comparative examples of the present invention, the testing method of the Prussian blue analogue is as follows:

[0042] According to the ratio of electrode material: conductive agent: binder = 7:2:1, weigh Prussian blue, Ketjen Black and super conductive carbon black (Super P) (each accounting for 50% of the conductive agent mass), polyvinylidene fluoride (PVDF), add a certain amount of N-methylpyrrolidone (NMP) as a solvent, and grind into a uniform slurry. The slurry is evenly coated on aluminum foil and then baked at 70°C for 24 hours. Finally, it is cut into small discs with a diameter of 8mm, and the electrode load is 1.6~2.4mg / cm 2 between.

[0043] The dried pole piece is placed in a 2032-type battery shell, with a sodium sheet as the negative electrode, glass fiber as the separator, and nickel foam as the support sheet. The electrolyte is 1 mol / L NaClO4 dissolved in 1:1 EC (ethylene carbonate) and DEC (diethyl carbonate), and 5% FEC (fluoroethylene carbonate) is added. The assembly is carried out in a glove box filled with argon, and the water content and oxygen content in the glove box are strictly controlled to be below 1ppm.

[0044] The packaged button cell was placed at room temperature for 8 hours and then tested with a CT2001 charge and discharge tester from Wuhan Blue Electric Company. The charge and discharge voltage was set to 2.0-4.2V. In the cycle performance test, the charge and discharge voltages were 0.2C and 5C (1C = 170mAg -1 ) multiples for testing.

[0045] Example 1

[0046] (1) Mix 6 g of anhydrous citric acid and 9 g of 1,3-bis(hydroxymethyl)urea and heat in an oil bath at 80°C until liquid;

[0047] (2) Pour 5 g of anhydrous sodium ferrocyanide (Na4Fe(CN)6) into a liquid eutectic solvent, stir the mixture in an 80°C oil bath for 12 h, and place the mixture in an 80°C oil bath for 12 h after the reaction is completed;

[0048] (3) After the reaction is completed, the mixture is cooled to room temperature, and the resulting blue solid mixture is washed three times with deionized water and anhydrous ethanol respectively by centrifugation;

[0049] (4) Dry in a vacuum oven at 100°C for 12 h to obtain Na 1.82 Fe[Fe(CN)6] 0.95 □ 0.05 0.74H2O (Fe-PBAs);

[0050] See also Figure 1 , Figure 1 The XRD pattern of Fe-PBAs synthesized in Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the Fe-PBAs synthesized in Example 1 of the present invention are a cubic Prussian blue structure. Since there is no influence of water molecules during the synthesis process and the solution viscosity is large, the crystallization rate of Prussian blue is low, defects can be effectively reduced, the molecular structure is more complete, the crystallinity is very high, and the structural water content is very low.

[0051] See also Figure 2 , Figure 2 This is a SEM photo of the Fe-PBAs synthesized in Example 1 of the present invention. Figure 2 It can be seen that the Fe-PBAs synthesized in Example 1 of the present invention are nano-sized, and their primary particle size is about 30 nm, which indicates that the high viscosity of the low eutectic solvent can effectively reduce the growth rate of Fe-PBAs, thereby reducing the particle size. Further component analysis shows that the sodium content of the Fe-PBAs is as high as 1.82 (theoretical value is 2), its low vacancy defect is as low as 5%, and the amount of crystal water is only 0.74.

[0052] The Fe-PBAs powder synthesized in Example 1 of the present invention was used as the positive electrode of a sodium ion battery to perform a battery performance test, and the obtained Figures 4-5 Experimental data shown. Figures 4-5 , Figure 4 and 5 The charge and discharge curves of the nano-Fe-PBAs synthesized in Example 1 of the present invention at 0.2C and 5C rates are shown respectively. Figures 4-5 It can be seen that the nano-Fe-PBAs synthesized in Example 1 of the present invention show excellent capacity utilization and kinetic performance. The first-cycle discharge specific capacity at a rate of 0.2C is 159 mAh / g, the first-cycle discharge specific capacity at a rate of 5C is 150 mAh / g, and the 5C capacity retention rate is 94% (1C = 170 mA / g).

[0053] Example 2

[0054] (1) Mix 6 g of anhydrous citric acid and 9 g of 1,3-bis(hydroxymethyl)urea and heat in an oil bath at 80°C until liquid;

[0055] (2) 3 g of anhydrous sodium ferrocyanide (Na4Fe(CN)6) and 3 g of anhydrous MnSO4 were poured into a liquid low eutectic solvent, and the mixture was stirred in an 80°C oil bath for 12 h. After the reaction was completed, the mixture was allowed to stand in an 80°C oil bath for 12 h;

[0056] (3) After the reaction is completed, the mixture is cooled to room temperature and washed three times with deionized water and anhydrous ethanol by centrifugation;

[0057] (4) Dry in a vacuum oven at 100°C for 12 h to obtain Na 1.72 Mn[Fe(CN)6] 0.91 □ 0.09 0.98H2O(Mn-PBAs).

[0058] Example 3

[0059] (1) Mix 6 g of anhydrous citric acid and 9 g of 1,3-bis(hydroxymethyl)urea and heat in an oil bath at 80°C until liquid;

[0060] (2) 3 g of anhydrous sodium ferrocyanide (Na4Fe(CN)6) and 6 g of anhydrous NiCl2 were poured into a liquid low eutectic solvent, and the mixture was stirred in an 80°C oil bath for 12 h. After the reaction was completed, the mixture was allowed to stand in an 80°C oil bath for 12 h;

[0061] (3) After the reaction is completed, the mixture is cooled to room temperature and washed three times with deionized water and anhydrous ethanol by centrifugation;

[0062] (4) Dry in a vacuum oven at 100°C for 12 h to obtain Na 1.68 Ni[Fe(CN)6] 0.97 □ 0.030.91H2O(Ni-PBAs).

[0063] Example 4

[0064] (1) Mix 5 g of ethylene glycol and 5 g of choline chloride and heat in an oil bath at 90°C until liquid;

[0065] (2) Pour 10 g of anhydrous sodium ferrocyanide (Na4Fe(CN)6) into a liquid eutectic solvent, stir the mixture in a 90°C oil bath for 12 h, and place it in a 90°C oil bath for 12 h after the reaction is completed;

[0066] (3) After the reaction is completed, the mixture is cooled to room temperature and washed three times with deionized water and anhydrous ethanol by centrifugation;

[0067] (4) Dry in a vacuum oven at 100°C for 12 h to obtain Na 1.78 Fe[Fe(CN)6] 0.90 □ 0.1 0.97H2O(Fe-PBAs).

[0068] Comparative Example 1

[0069] (1) Mix 6 g of anhydrous citric acid and 9 g of 1,3-bis(hydroxymethyl)urea and heat in an oil bath at 100°C until liquid;

[0070] (2) Pour 5 g of anhydrous sodium ferrocyanide (Na4Fe(CN)6) into a liquid eutectic solvent, stir the mixture in an oil bath at 100°C for 12 h, and after the reaction is completed, leave it in an oil bath at 100°C for 12 h;

[0071] (3) After the reaction is completed, the mixture is cooled to room temperature, and the resulting blue solid mixture is washed three times with deionized water and anhydrous ethanol respectively by centrifugation;

[0072] (4) Dry in a vacuum oven at 100°C for 12 h to obtain Na 1.52 Fe[Fe(CN)6] 0.92 □ 0.08 0.89H2O(Fe-PBAs).

[0073] See also Figure 3 , Figure 3 : is a SEM photo of Fe-PBAs synthesized in Comparative Example 1 of the present invention. Figure 3 It can be seen that the primary particle size of Fe-PBAs is about 50nm, which indicates that when the temperature increases, the viscosity of the low eutectic solvent decreases, resulting in an accelerated growth rate of Fe-PBAs and a larger particle size. Composition analysis shows that the sodium content of the Fe-PBAs is 1.52, its low vacancy defect is 8%, and the number of crystal water is 0.89.

[0074] The Fe-PBAs powder synthesized in Comparative Example 1 of the present invention was used as the positive electrode of a sodium ion battery to perform a battery performance test, and the obtained Figures 6-7 Experimental data shown. Figures 6-7 , Figure 6 and 7 The charge and discharge curves of the nano-Fe-PBAs synthesized in Comparative Example 1 of the present invention at 0.2C and 5C rates are shown respectively. Figures 6-7 It can be seen that the capacity and kinetic performance of the nano-Fe-PBAs synthesized in Comparative Example 1 of the present invention are significantly worse than those in Example 1. The first-cycle discharge capacity at a rate of 0.2C is 135 mAh / g, the first-cycle discharge capacity at a rate of 5C is 107 mAh / g, and the 5C capacity retention rate is 79% (1C = 170 mA / g).

[0075] Compared with the prior art, the beneficial effects of the present invention include:

[0076] (1) The eutectic reagent used in the present invention is simple to prepare, has good chemical and physical stability, good solubility in metal salts, and adjustable viscosity and melting point, and is therefore an excellent reaction medium;

[0077] (2) The low eutectic solvent used in the present invention is liquid above the melting point and solid below the melting point. Its viscosity can be adjusted by temperature, thereby regulating the crystallization rate of PBAs. At high viscosity, the structural integrity of PBAs is higher and the primary grains are smaller;

[0078] (3) The synthesis of PBAs of the present invention is carried out in an anhydrous environment, which can more effectively reduce the adverse effects of water molecules on their structure;

[0079] (4) The synthesis of PBAs of the present invention does not require the use of a large amount of complexing agent, which can reduce the cost of raw materials.

[0080] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a Prussian blue analogue, characterized in that: The following steps are involved: The raw materials for forming a deep eutectic solvent are mixed and heated to a target temperature to obtain a high-viscosity liquid deep eutectic solvent; The high-viscosity liquid low eutectic solvent is mixed with sodium ferrocyanide and an optional metal salt at a target temperature for reaction, and high-quality Na x M[Fe(CN)6] y □ 1-y · zH2O; Wherein, M is at least one of transition metals Fe, Cu, Ni, Mn and Co, □ is a low spin vacancy defect, 0 < x < 2, 0 < y < 1, 0 < z < 2; the low eutectic solvent is a low eutectic solvent formed by citric acid and 1,3-bishydroxymethyl urea or a low eutectic solvent formed by ethylene glycol and choline chloride; the melting point of the low eutectic solvent is 60~85°C; the target temperature is 5~20°C above the melting point of the low eutectic solvent.

2. The method for preparing a Prussian blue analogue according to claim 1, characterized in that: The deep eutectic solvent is a deep eutectic solvent formed by 40 wt % of citric acid and 60 wt % of 1,3-bis(hydroxymethyl)urea or a deep eutectic solvent formed by 50 wt % of ethylene glycol and 50 wt % of choline chloride.

3. The method for preparing the Prussian blue analogue according to claim 1, characterized in that: The mass ratio of the sodium ferrocyanide, the metal salt and the low eutectic solvent is (20~100): (0~100):

100.

4. The method for preparing a Prussian blue analogue according to claim 1, characterized in that: The high viscosity liquid deep eutectic solvent is mixed with sodium ferrocyanide and an optional metal salt at a target temperature to react, comprising: A high viscosity liquid low eutectic solvent is reacted with sodium ferrocyanide (Na4Fe(CN)6) and an optional metal salt under stirring at a target temperature for 8 to 24 hours, and then allowed to stand and age at the target temperature for 8 to 24 hours.

5. The method for preparing the Prussian blue analogue according to claim 1, characterized in that: The Na x M[Fe(CN)6] y □ 1-y ·zH2O, where 1 < x < 2, 0.9 < y < 1, 0 < z < 1, and the size of the Prussian blue analogue is 10 - 100 nm.

6. A Prussian blue analogue, characterized in that The Prussian blue analogue is obtained by the preparation method of the Prussian blue analogue according to any one of claims 1 to 5.

7. A use of a Prussian blue analogue, characterized in that: The Prussian blue analogue as claimed in claim 6 is used as a positive electrode material for a sodium ion battery.